Alteration of the Sitting and Standing Movement in Adult Spinal Deformity - Saad, Eddy; Semaan, Karl; Kawkabani, Georges; Massaad, Abir; Salibv, Renee Maria; Mekhael, Mario; Fakhoury, Marc; Karam, Krystel Abi; Jaber, Elena; Ghanem, Ismat; Lafage, Virginie; Skalli, Wafa; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Adults with spinal deformity (ASD) are known to have spinal malalignment affecting their quality of life and daily life activities. While walking kinematics were shown to be altered in ASD, other functional activities are yet to be evaluated such as sitting and standing which are essential for patients’ autonomy and quality of life perception. In this cross-sectional study, 93 ASD subjects (50±20years; 71F) age and sex matched to 31 controls (45±15years; 18F) underwent biplanar radiographic imaging with subsequent calculation of standing radiographic spinopelvic parameters. All subjects filled HRQOL questionnaires such as SF36 and ODI. ASD were further divided into 34 ASD-sag (with PT>25° and/or SVA>5cm and/or PI-LL>10°), 32 ASD-hyperTK (with only TK>60°) and 27 ASD-front (with only frontal malalignment: Cobb>20°). All subjects underwent 3D motion analysis during the sit-to-stand and stand-to-sit movements. The range of motion (ROM) and mean values of pelvis, lower limbs, thorax, head and spinal segments were calculated on the kinematic waveforms. Kinematics were compared between groups and correlations to radiographic and HRQOL scores were computed. During sit-to-stand and stand-to-sit movements, ASD-sag had decreased pelvic anteversion (12.2° vs 15.2°), hip flexion (53.0° vs 62.2°), sagittal mobility in knees (87.1° vs 93.9°) and lumbar mobility (L1L3-L3L5: -9.1° vs -6.8°, all p<0.05) compared to controls. ASD-hyperTK showed increased dynamic lordosis (L1L3-L3L5: -9.1° vs -6.8°), segmental thoracic kyphosis (T2T10-T10L1: 32.0° vs 17.2°, C7T2-T2T10: 30.4° vs 17.7°) and thoracolumbar extension (T10L1-L1L3: -12.4° vs -5.5°, all p<0.05) compared to controls. They also had increased mobility at the thoracolumbar and upper-thoracic spine. Both ASD-sag and ASD-hyperTK maintained a flexed trunk, an extended head along with an increased trunk and head sagittal ROM. Kinematic alterations were correlated to radiographic parameters and HRQOL scores. Even after controlling for demographic factors, dynamic trunk flexion was determined by TK and PI-LL mismatch (adj.R2=0.44). Lumbar sagittal ROM was determined by PI-LL mismatch (adj.R2=0.13). In conclusion, the type of spinal deformity in ASD seem to determine the strategy used for sitting and standing. Future studies should evaluate whether surgical correction of the deformity could restore sitting and standing kinematics and ultimately improve quality of life.